Reactogenicity and immunogenicity of the intradermal administration of BNT162b2 mRNA vaccine in healthy adults who were primed with an inactivated SARS-CoV-2 vaccine - Yutthapong Temtanakitpaisan; Suchaorn Saengnipanthkul; Nataporn Sarakosol; Sasinapa Maskasame; Siwawoot Mongkon; Benjaporn Buranrat; Sutthiwan Thammawat; Samadhi Patamatamkul; Pattaranit Nernsai (Vaccine: X, 2022)
Because of the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), safe and effective vaccines are urgently required. The shortage of effective vaccines is a major challenge in many developing countries. We studied intradermal (ID) fractional dose BNT162b2 mRNA (Comirnaty®, Pfizer-BioNTech) as a booster dose in healthy adults who were previously immunized with an inactivated SARS-CoV-2 vaccine. This is a retrospective cohort study that included healthy adults who were immunized with two doses of inactivated SARS-CoV-2 vaccine and received a booster dose with ID fractional dose or intramuscular (IM) full-dose BNT162b2 mRNA between August 1 to August 15, 2021. The primary endpoint was safety that included local and systemic adverse reactions. The secondary endpoints were levels of SARS-CoV-2 spike protein receptor-binding domain IgG antibody (anti-S-RBD IgG) and neutralizing antibody activity against the Delta variant (B.1.617.2) using surrogate viral neutralization test (sVNT) 3 weeks after the booster dose. A total of 43 healthy adults (median age of 31 years) were included in the study; among them, 23 participants received ID fractional dose (6 µg) BNT162b2 mRNA, and 20 participants received IM full-dose (30 µg) BNT162b2 mRNA. No serious adverse reactions were observed. Local adverse reactions occurred more frequently in the ID group. No differences were observed in the baseline level of anti-S-RBD IgG (289 vs 286 AU/mL, p > 0.9, in the ID and IM groups, respectively). After booster, anti-S-RBD IgG titer increased to 13294 (9255–19573) AU/mL in the ID group and 23456 (16943–38539) AU/mL in the IM group. All participants in the IM group and 95.6 % of participants in the ID group had seroconversion evaluated by sVNT (≥68 % inhibition to the Delta variant). ID administration of BNT162b2 mRNA was safe and well-tolerated and generated a robust immune response. Therefore, ID delivery of the BNT162b2 mRNA vaccine has the potential for a dose-sparing strategy.